Answer:
![y = -2x](https://img.qammunity.org/2021/formulas/mathematics/middle-school/1gfkuojrpnkyt449yknahu2zbs0b4yw5xz.png)
Explanation:
Given
x || 0 || 1 || -2
y || 0 || -2 || 4
Required
Determine the function rule
First, we have to determine the slope of the function using;
![m = (y_1 - y_2)/(x_1 - x_2)](https://img.qammunity.org/2021/formulas/mathematics/college/w03yns66ehvnlkqoh0irr329qt7f626lrt.png)
Where x and y represent any two corresponding values of x and y
When x = 0; y = 0
![(x_1,y_1)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/8imohudcnvb15ycufziosbchsdnshey65k.png)
When x = 1; y = -2
![(x_2,y_2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/afjoih3inj41891gm82w4t44k4qifaxvdd.png)
Substitute these values in
![m = (y_1 - y_2)/(x_1 - x_2)](https://img.qammunity.org/2021/formulas/mathematics/college/w03yns66ehvnlkqoh0irr329qt7f626lrt.png)
![m = (0 - (-2))/(0 - 1)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/3rokb7mth1bcnsuwl3fdjo30qvw08kcraf.png)
![m = (0 +2)/(0 - 1)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/2vrgjq15ikwd1jra0hpiwyvehejfv7z12m.png)
![m = (2)/(- 1)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/yunuom9iumsu0fcx61dpmlqefcy75qcbox.png)
![m = -2](https://img.qammunity.org/2021/formulas/mathematics/high-school/mhy29wapueh4dzsdd6u1hynxs4nw2tlck5.png)
Next, is to determine the function rule; using slope intercept form as follows;
![y - y_1 = m(x - x_1)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/114ibzuj57ml08mu59z59vjg3t4kik0hxk.png)
Take any corresponding values of x and y as x1 and x2
When x = -2; y = 4
becomes
![y - 4 = -2(x - (-2))](https://img.qammunity.org/2021/formulas/mathematics/middle-school/j6fbs0o8qxqn4ghdpf8cxho83kvzqg6vnv.png)
![y - 4 = -2(x + 2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/u3etgtzx2uep9djahyvt116peusfndmhd1.png)
Open the bracket
![y - 4 = -2x -4](https://img.qammunity.org/2021/formulas/mathematics/middle-school/fsd90gk5jy8bfz8vtl6l9ctnbiwwfns448.png)
Add 4 to both sides
![y - 4 + 4 = -2x - 4 + 4](https://img.qammunity.org/2021/formulas/mathematics/middle-school/wx1qqdovf98j0crll4gwegz1l2aelim7z8.png)
![y = -2x](https://img.qammunity.org/2021/formulas/mathematics/middle-school/1gfkuojrpnkyt449yknahu2zbs0b4yw5xz.png)
Hence, the function rule is
![y = -2x](https://img.qammunity.org/2021/formulas/mathematics/middle-school/1gfkuojrpnkyt449yknahu2zbs0b4yw5xz.png)